Preferences factors of the customers by choosing Sanrio Hello Kitty Town and Thomas Town at Puteri Harbour from management perspective / Qistina Rosli - Rosli, Qistina (Faculty of Business and Management, 2018)
As we know Malaysia has a lot of theme park to be explore. In 2018 the theme park in Malaysia now become a trend as a reaction with their friends, couple and family. The theme park also give a contribution as the tourism and attraction to the country. Sanrio Hello Kitty Town and Thomas Town is the well known brand of character theme park. Due to the increase of the opening theme park development in Johor, The Sanrio Hello Kitty Town & Thomas Town start to shaking. The number of attendance start to decline day by day. It is because the competition between the others theme park is very high in Johor. The objective of this study is to identify the preferences factors of the customers by choosing Sanrio Hello Kitty Town and Thomas Town at Puteri Harbour from management perspective and to determine the most factor contribute to the preference of customers towards Sanrio Hello Kitty Town and Thomas Town Puteri Harbour from management perspective. This research has been conducted by the support of primary data and secondary data. The methodology of this study is by using qualitative research with interviewing the permanent staff off TAR PH Holdings Sdn. Bhd. (Sanrio Hello Kitty and Thomas Town) as the data collection for primary data. For secondary data researcher use external sources such as online journals, books, and internet sources. This research has four preferences factors of customer by choosing Sanrio Hello Kitty Town and Thomas Town as their theme park destination. The factor are by strong marketing, roadshow & sales promotion, Brand image & brand awareness and lastly is social media. The findings show that both of the factor contribute to the preferences except for brand awareness has a gap with the findings. Besides that the researcher also comes out with a few recommendation to solve the problem that face the company.